A simple and sensitive fluoroimmunoassay based on the nanobody-alkaline phosphatase fusion protein for the rapid detection of fenitrothion - Chen, Zi-Jian; Huang, Ai-Jun; Dong, Xiu-Xiu; Zhang, Yi-Feng; Zhu, Lin; Luo, Lin; Xu, Zhen-Lin; Wang, Hongwu (Frontiers in Sustainable Food Systems, 2023)
Immunoassay is a powerful tool for the rapid detection of small harmful organic molecules. In this study, a simple and sensitive fluoroimmunoassay (FIA) based on a nanobody-alkaline phosphatase fusion protein (VHHjd8-ALP) and blue-emissive carbon dots (bCDs) was developed for the rapid detection of fenitrothion. The bCDs were synthesized using the one-step hydrothermal method. Citric acid and urea were used as carbon and nitrogen sources, respectively. The synthesized bCDs were characterized by fluorescence spectrum, high-resolution transmission electron microscopy, x-ray photoelectron spectroscopy, and Fourier transform infrared spectroscopy. After one step of competitive immunoassay, the VHHjd8-ALP bound to the microplate and catalyzed the substrate p-nitrophenylphosphate (pNPP) into p-nitrophenol (pNP); the latter can quench the blue of bCDs due to an inner-filter effect. After condition optimization, an FIA calibration curve was finally created, which showed an IC50 value of 16.25 ng/mL and a limit of detection (LOD) of 0.19 ng/mL. Compared with the pNPP-based one-step conventional indirect competitive enzyme-linked immunoassay (icELISA), the developed FIA showed an 11-fold sensitivity improvement. Furthermore, the analysis period of FIA only takes approximately 55 min, which was obviously faster than that of the conventional icELISA. The recovery test showed recoveries from 81.8 to 119% with fruits and vegetable samples, which verified the practicability and accuracy of the developed FIA.